PENINGKATAN KEMANDIRIAN ANAK USIA 4-5 TAHUN MELALUI KEGIATAN PRACTICAL LIFE DI PAUD TUNAS BANGSA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to increase children's independence through practical life activities in early childhood. Independence is a crucial aspect that needs to be developed from an early age because it influences their social, emotional, and cognitive development. However, based on initial observations, many children still rely on teachers for daily activities. This study used the Classroom Action Research (CAR) method, implemented in two cycles, each consisting of planning, implementation, observation, and reflection. Twenty children participated in the study. Data collection techniques used observation and documentation, while data analysis was conducted using percentage techniques. The results showed that children's independence increased in each cycle. In cycle I, most children were still in the "beginning to develop" category. Meanwhile, in cycle II, significant improvement occurred, with most children reaching the "developing" category as expected and developing very well. This improvement occurred because children began to become accustomed to carrying out practical life activities independently. Thus, practical life activities have proven effective in increasing children's independence and can be used as an alternative learning strategy in early childhood education (PAUD).